PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS YOUTUBE DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Yulistian, Yulistian; Bahrudin, Febrian Alwan; Lestari, Ria Yuni (Academy of Education Journal, 2023)
This study aims to determine whether there are differences in students' learning interests, and to determine whether there is influence of YouTube media on students' learning interests in learning Pancasila and Citizenship Education. This study uses a quantitative approach, with a “quasi experimental” method. The population is class XI students of SMA Negeri 1 Pabuaran with a total of 241 students. The samples used were 58 samples taken from control class and experimental class. The results showed that there was a significant difference between the results of the learning interest of the experimental class and the control class with the results of the independent sample T-test obtained a significance value (2-tailed) of 0.000 > 0.05. In the linear regression results, the results obtained were Tcount > Ttable, namely (4.650 > 1.701), so that the YouTube media had a significant effect on the learning interest of the experimental class students.